Rancang Bangun Sistem E-Learning SMK Negeri 5 Padang - Prioga Desparo; Ika Parma Dewi; Dedy Irfan; Mahesi Agni Zaus; Rizkayeni Marta (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to design and develop a web-based e-learning system as a supporting medium for learning in the Computer and Network Engineering Department at SMK Negeri 5 Padang. The problems identified include the absence of an integrated digital learning system, limited access to learning materials outside the classroom, and conventional management of assignments and communication. This study employs a Research and Development (R&D) method with the System Development Life Cycle (SDLC) using the Waterfall approach, which consists of analysis, design, implementation, and testing stages. System design is carried out using Unified Modeling Language (UML), while implementation utilizes the PHP programming language supported by tools such as Laragon, Composer, and Node.js. System testing is conducted using the Black Box Testing method to ensure that all functionalities operate according to requirements. The results indicate that the developed e-learning system is capable of facilitating learning material management, assignment submission and assessment, photo-based attendance, and integrated announcement delivery. The system is considered to improve flexibility, effectiveness, and accessibility of the learning process without replacing face-to-face learning. Therefore, this web-based e-learning system can serve as an alternative solution to support learning activities at SMK Negeri 5 Padang.